MOTILITAS DAN VIABILITAS SPERMATOZOA BABI DENGAN HOLDING TIME DAN LAMA THAWING BERBEDA (Sperm motility and viability of boars in different holding and thawing time) - Ni Luh Manik Sugiantini; Ni Luh Gde Sumardani; I Wayan Suberata (JURNAL NUKLEUS PETERNAKAN, 2023)
The motility and viability of sperm are the main factors in determining semen quality. The treatment of semen before and after dilution is a determining factor whether or not the semen is suitable for use in artificial insemination. This study aims to determine the effect of holding time and thawing time on the motility and viability of boars sperm. This research was conducted at the Livestock Reproduction Laboratory, Bukit Jimbaran for 1 month, using a factorial randomized block design The first factor is the holding time which consists of 3 levels: 0 hours (HT0), 2 hours (HT2), and 3 hours (HT3). The second factor is the thawing time which consists of 3 levels: for 2 minutes (T2), 3 minutes (T3), and 5 minutes (T5). There are 9 combinations and 5 groups based on sperm storage time. The observed variables included the motility and viability of boars sperm. The results showed that the HT3 treatment was significantly different (P<0.05) with 22% sperm motility and 41.55% sperm viability. Thawing for 5 minutes (T5) gave the best results with sperm motility 18.50% and sperm viability 38.45%. There was no interaction between holding time and thawing time. The conclusion of this study is that boars sperm shows the best results at holding time of 3 hours with a thawing time of 5 minutes.